Development of a Highly Specific and Sensitive Latex Agglutination Test for the Detection of Caprine Mycoplasmosis - P. Santhiya; Surya Sankar; V. Niranjana; V. Athira; R. T. Venkatachelapathy; M. Mini; A. Bosewell (Indian Journal of Microbiology, 2026)

Metabolic alterations in moderately resistant West Coast Tall and susceptible Chowghat Orange Dwarf coconut varieties in response to exotic whitefly infestation - P. Logeshkumar; R. Nalini; M.L. Mini; S. Vellaikumar; A. Josephrajkumar; M. Murugan; M. Paramasivam (Arthropod-Plant Interactions, 2025)

International Consortium on Ageing-Related Pathologies (ICCARP) Audiovestibular Group: fostering international consensus to refine International Classification of Diseases (ICD-11) codes for hearing loss across the life course - Dialechti Tsimpida; Michael A. Akeroyd; Barry L. Bentley; Shuvarthi Bhattacharjee; Michael R. Bowl; Emma Broome; Stuart R. G. Calimport; Sian Calvert; Gary Christopher; Tom Dening; Silvia Di Bonaventura; Ankita Goswami; et al. (GeroScience, 2025)

Insights into the incidence, severity and morphometrics of the invasive Rugose Spiralling Whitefly Aleurodicus rugioperculatus Martin in coconut belts of Tamil Nadu, India - P. Logeshkumar; R. Nalini; A. Josephrajkumar; P. Chandramani; M. L. Mini; R. Durai Singh; K. Venkatesh; M. Murugan (International Journal of Tropical Insect Science, 2024)

Multi-wave characteristics associated with January 15, 2022 Hunga-Tonga volcanic eruption: A global observation - M.S. Rose; P.S. Sunil; A. Sooraj; A.S. Sunil; Priyesh Kunnummal; K. Amal George; K.K. Ajith; Dhanya Thomas; V.K. Mini (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Untangling the taxonomic ambiguities of the spotted seerfish Scomberomorus guttatus with the description of a new species from India - Eruppakkottil M. Abdussamad; Thomas Toji; Amalraj M. R. Margaret; Kalappurakkal G. Mini; Kothanahally M. Rajesh; Pokkathappada A. Azeez; Vinothkumar Ramar; Thayichira B. Retheesh; Athikkattil M. Abbas; Ismail Shihab; Sneha M. George; Rohith Prathibha; et al. (Journal of Fish Biology, 2024)
Scomberomorus guttatus has been subjected to a series of synonym assignations over the years. Its taxonomy has been mired with ambiguities due to the greater‐than‐average morphological variations observed in samples from different regions. An integrated taxonomic revision with molecular support indicated that the species that was thought to be a single entity, in reality, is a complex of three distinct species. They are morphologically distinct with respect to the body depth and elongation, cephalic morphometry, and meristic characteristics. Otolith morphometry and phylogenetic evidence further established the taxonomic divergence within the spotted seerfish complex. The phylogenetic characteristic as indicated by the mitochondrial Cytochrome c Oxidase subunit I (COI) sequence unveiled that S. guttatus had a high intraspecific divergence of 11.1% from its two identical congeners and a divergence of 2.34% between the congeners, indicating scope for categorizing them as separate species. Based on the morphological and molecular evidence, S. guttatus is redescribed; the senior synonym Scomberomorus leopardus is resurrected as a valid species; and a new species Scomberomorus avirostrus n. sp. is described with keys for species distinction.

Fish Catch Survey and Analysis – An online application for deriving measures and indicators for fish stock assessment - Mini K.G.; Sathianandan T.V.; Somy Kuriakose; Sindhu K. Augustine; Manu V.K.; Manjeesh R.; Sijo Paul; Jayasankar J.; Eldho Varghese; Gopalakrishnan A. (Fisheries Research, 2023)

Age and Growth Studies in Indian Oil Sardine (Sardinella longiceps) using Hard Part Microstructure, a Tool for Biological and Ecological Understanding - E. M. Abdussamad; P. Rohit; S. Ghosh; K. G. Mini; P. Shameer; N. V. Dipti; T. B. Retheesh; A. M. Abbas; A. R. Akhil; I. Shihab; A. Gopalakrishnan (Thalassas: An International Journal of Marine Sciences, 2023)

Monitoring of Harmful Algal Bloom (HAB) of Noctiluca scintillans (Macartney) along the Gulf of Mannar, India using in-situ and satellite observations and its impact on wild and maricultured finfishes - Rameshkumar. P; P.S. Thirumalaiselvan; Mini Raman; L. Remya; R. Jayakumar; M. Sakthivel; G. Tamilmani; M. Sankar; K.K. Anikuttan; N. Nandini Menon; Raju Saravanan; T.T. Ravikumar; et al. (Marine Pollution Bulletin, 2023)

SAtellite-based Marine Process Understanding, Development, Research and Applications for Blue Economy (SAMUDRA): A Technology Demonstration Program in the Bay of Bengal - Rashmi Sharma; Neeraj Agarwal; Ratheesh R; Surisetty VVArun Kumar; A. D. Rao; KVSR Prasad; Jaya Kumar Seelam; R. Mani Murali; V. Suneel; Surendra Singh K; R. K. Sarangi; Soba J. Kizhakudan; et al. (Journal of the Indian Society of Remote Sensing, 2023)

Early detection of heavy rainfall events associated with the monsoon in Kerala, India using GPS derived ZTD and PWV estimates: A case study - M S Rose; P S Sunil; Johnson Zacharia; K M Sreejith; S Sunda; V K Mini; A S Sunil; K Vijay Kumar (Journal of Earth System Science, 2023)

Empirically derived Coloured Dissolved Organic Matter absorption coefficient using in-situ and Sentinel 3/OLCI in coastal waters of India - Arvind Sahay; Syed Moosa Ali; Mini Raman; Anurag Gupta; Gunjan Motwani; Rohan Thakker; Anima Tirkey; Hitesh A. Solanki; Palanisamy Shanmugam (International Journal of Remote Sensing, 2022)

Trends in climate extremes at local farming calendar timescale: evidence from Merti District, Ethiopia - B. Wubishaw Endale; E. Mini Simphiwe; A. Abegaz Yimer (Modeling Earth Systems and Environment, 2021)

A new paradigm for short-range forecasting of severe weather over the Indian region - Soma Sen Roy; Pradeep Sharma; Bikram Sen; K. Sathi Devi; S. Sunitha Devi; Neetha K. Gopal; Naresh Kumar; Krishna Mishra; Shobhit Katyar; Surendra Pratap Singh; Shibin Balakrishnan; Charan Singh; et al. (Meteorology and Atmospheric Physics, 2021)

Using crop growth model stress covariates and AMMI decomposition to better predict genotype-by-environment interactions - R. Rincent; M. Malosetti; B. Ababaei; G. Touzy; A. Mini; M. Bogard; P. Martre; J. Le Gouis; F. van Eeuwijk (Theoretical and Applied Genetics, 2019)

Fecal calprotectin concentrations in cancer patients with Clostridium difficile infection - Taojun He; Samuel E. Kaplan; Luz A. Gomez; Xuedong Lu; Lakshmi V. Ramanathan; Mini Kamboj; Yi-Wei Tang (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

A regional algorithm to model mesozooplankton biomass along the southwestern Bay of Bengal - R. Mahesh; A. Saravanakumar; T. Thangaradjou; H. U. Solanki; Mini Raman (Environmental Monitoring and Assessment, 2018)

Comparative transcriptome analyses reveal conserved and distinct mechanisms in ovine and bovine lactation - Mini Singh; Peter C. Thomson; Paul A. Sheehy; Herman W. Raadsma (Functional & Integrative Genomics, 2013)

In vitro antiperoxidative, free radical scavenging and xanthine oxidase inhibitory potentials of ethyl acetate fraction of Saraca ashoka flowers - A. Prathapan; O. Lijo Cherian; Suresh V. Nampoothiri; S. Mini; K.G. Raghu (Natural Product Research, 2011)

Micropropagation of camphor tree (Cinnamomum camphora) - K. Nirmal Babu; A. Sajina; D. Minoo; C.Z. John; P.M. Mini; K.V. Tushar; J. Rema; P.N. Ravindran (Plant Cell, Tissue and Organ Culture (PCTOC), 2003)